Urgensi Hermeneutics Hukum dalam Metode Interpretasi Hukum Lain Perspektif Filosofis Hans George Gadamer - Ismiati, Euis I.; Ollong, Emy (Green Publisher Indonesia, 2025)
Legal discovery (rechtsvinding) by judges and legal practitioners never occurs in a vacuum. Legal texts, as products of the past, often present ambiguities when confronted with the complexity of current cases and issues. With conventional legal interpretation methods such as grammatical, historical, and systematic, although fundamental, they tend to treat the text as a static object and often ignore the crucial role of the interpreter. This stydy aims to elaborate on the urgency of legal hermeneutics, as proposed by Hnas George Gdamer, as a philosophical approach that transcends the limitations of these methods. Using a qualitative literature study, namely pre-understanding (vorurteil), horizon fusion (horizontverschmelzung), and application (anwendung). The results of the analysis show that Gadamer rejects the positivistic view that rigidly separates the subject (interpreter) and the object (text). Gadamer’s perspective, every interpreter always brings with him a “pre-understanding” fomed from tradition and history which is not a barrier, but rather from the starting point of understanding (interpretation) and application (application) of lawi s one inserparable moment. In this case, the judge not only “discovers” the hidden (inherent) meaning but also participates in producing legal meaning that is relevant to the concrete situation and hand. Therefore, Gadamer’s hermeneutics offers a more authentic philosophical foundation for the practice of legal discovery, recognizing the dynamics between legal tradition and the demands of contemporary justice.